AKTIVITAS KOMUNIKASI PEMASARAN PT ARAH DUNIA TELEVISI PADA PROGRAM RAMADHANKU DI JOGJA - Tasya Yuni Azzahra; Berlian Primadani Satria Putri (Universitas Lambung Mangkurat, 2023)
In the current digital era, new media, such as social media, have emerged abundantly. These new media platforms serve similar functions to television, providing information and entertainment, and can be seen as potential substitutes for television due to their accessibility and availability anywhere. To remain relevant in this evolving era, television networks have adapted to the trends by shifting towards digital television that can be accessed through gadgets. ADITV is one of the local Islamic television stations in Yogyakarta that has made this transition to digital television. One of ADITV's programs that reflects its Islamic identity is